AKTIVITAS MAHASISWA DI LUAR KAMPUS DALAM UNGKAP KARYA SENI LUKIS KONTEMPORER - ANDRES PERMADI, Drs. Idran Wakidi, Yasrul Sami, S.Sn., M.Sn (Serupa The Journal of Art Education, 2015)
Students have the role and function in society are growing. Student mustpossess responsibility, skilled and hardworking between lectures with off-campus activities. Activity outside the campus has many varieties, such as working as an employee or self-employed as well, following the organization's activities, hobbies, and develop the skills possessed. College while working or other activities outside the campus is a new alternative to train independence, adds to the experience, as well as other science that can deliver a step in the era of contemporary society. From Students like is what lies behind the writer to put it on the painting with the title "Off Campus Student Activity In Reveal Work of Contemporary Art".From a variety of diverse activities off-campus students, this thesispresents the visualization of off-campus student activities in the style ofcontemporary painting with the addition of some supporting objects and use materials watercolor on canvas. Preparation, elaboration of ideas, synthesis, and realize the concept of the major steps in determining each of the works right idea, to the purpose in creating the final masterpiece. This final work featuring portraits of students who represent the themes and concepts appropriate to the work of the author. Any objects that appear to have a relationship with the object of supporting the one and the other. This thesis also emphasizes the cultivation of the realist techniques and heighten dimensional shape of the object.The final work will be invited to the current students to always lookcreative in conducting lectures and off-campus activities. Activity outside the campus will provide a fresh new look that gave birth to the experience and skills of a student yourself. Course of a positive activity, ready to become a weapon in the face of competition stepped life in society. Students Thus, the authors visualize the work of art as a reflection in the learning process for writers and other students.Keywords: Student Activity, Painting